Gay and lesbian literature disrupting the heteronormative space of the high school english classroom - Helmer, Kirsten (Sex Education: Sexuality, Society and Learning, 2016)
This paper offers insights into how the teaching of queer topics in English language arts classes can be reframed by bridging the goals, practices and conceptual tools of queer theory to literacy teaching. Drawing on an ethnographic classroom study, which explored a 13-week high school Gay and Lesbian Literature course, this paper discusses how teaching an English literature curriculum centred on the voices and stories of LGBTQI people constitutes a meaningful site for learning and teaching. In the process, I show how a queer-themed literature curriculum not only intervenes disruptively into the heteronormative space of school through its content but also through pedagogical practices that open up new lines of thinking for understanding diverse sexualities and genders. Through vignettes from the classroom, I illustrate how queer moments were enacted in this high school course as the class (a) deconstructed literary and media texts; (b) used moments of discomfort for learning; (c) produced counter-narratives through creative acts; and (d) engaged in experiential learning activities that troubled commonsense understandings of sexuality, sex and gender. The paper aims to provide educators and administrators with ideas on how a comprehensive queer-inclusive English literature curriculum can be implemented in high schools.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; genre; identités LGBTQIA2+; pédagogie; périodes historiques; queer; régions géographiques; sexualité; thématiques; école secondaire; états-unis

Se retrouver entre soi pour se reconnaitre: conceptions du genre et regulation des echanges dans un forum de personnes trans - Pastinelli, Madeleine; Dery, Caroline (Anthropologie et Societes, 2016)
Les possibilités de communication anonyme permises par les nouvelles technologies amènent des personnes qui ont en commun des pratiques ou des expériences qui les stigmatisent à se retrouver à l’abri des regards pour échanger entre elles et former des communautés en ligne. Ce faisant, elles se réapproprient leur expérience dans un langage choisi qui leur permet de redonner sens à des identités et des pratiques marginales ou considérées comme déviantes ou pensées comme relevant de la pathologie par le discours médical. L’enquête que nous avons menée dans une communauté en ligne de personnes trans éclaire la manière dont la fréquentation de celle-ci permet à ces personnes de se (re)connaître dans leur expérience particulière du corps et du genre et de faire sens de cette expérience. La volonté communément partagée par ces personnes de penser autrement leur expérience donne lieu à la rencontre d’une multitude de conceptions différentes, et parfois incompatibles entre elles, de l’identité de genre et de l’expérience trans. L’analyse se penche plus particulièrement sur la régulation du discours et des échanges qui est faite par les modérateurs dans ce contexte et sur le type de consensus qu’elle rend possible.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; hétérosexisme; identités LGBTQIA2+; outils; premier cycle; pédagogie; périodes historiques; queer; québec; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; transféminisme